Correlation Between Body Mass Index and Serum Uric Acid Among Healthy Pakistani Adults: A Cross-Sectional Comparative Study - Naveed Ahsan, Aneel Kapoor, Mona Rani, Ghulam Serwar Shaikh, Shahid Zafar, Vinay Kumar Jesrani (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the relationship between body mass index and serum uric acid among healthy Pakistani adults Study design: A cross-sectional comparative study Place and Duration This study was conducted in Bakhtawar Amin Medical and Dental College Multan from November 2020 to April 2022 Methodology:A total of 250 subjects were randomly recruited out of which 120 subjects were selected in this study. Each group comprised 60 subjects. Group A comprised healthy controls subjects, while Group B comprised hyperuricemic persons with no complaints. By dividing body weight (kg) by the square of height, the BMI was computed. We divided BMI into three categories using diagnostic criteria for obesity in Asian populations given by the WHO. Participants’ fasting blood samples (5 mL) were taken under stringent aseptic conditions to measure the serum uric acid level Version 23.0 of IBM-SPSS was used to store and analyse the data, Counts with percentages were reported on gender and BMI classifications between the two studied groups, and Mean with standard deviation were given for BMI and serum uric acid. Results:In the present study in group A 66.7% were male gender, 63.3% were overweight, mean BMI was 24.2 (SD=±2.0) kg/m2, and mean serum uric acid was 4.5 (SD=±0.6) units, whereas in group B there were 60% male gender, 70% were overweight, mean BMI was 23.6 (SD=±1.4) and mean serum uric acid was 8.1 (SD=±0.6) units. The independent sample test gives a significant mean difference in serum uric acid between group A and B samples with p<0.05. Conclusion: The study’s findings show no significant correlation between serum uric acid, overweight and obesity among the Pakistani adult population. Keywords: Body Mass Index, serum uric acid, Pakistan, adults, overweight